2023
DOI: 10.1111/pbi.14009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TaGL1‐B1 gene controlling grain length through regulation of jasmonic acid in common wheat

Abstract: Summary Grain length is one of the most important factors in determining wheat yield. Here, a stable QTL for grain length was mapped on chromosome 1B in a F10 recombinant inbred lines (RIL) population, and the gene TaGL1‐B1 encoding carotenoid isomerase was identified in a secondary large population through multiple strategies. The genome‐wide association study (GWAS) in 243 wheat accessions revealed that the marker for TaGL1‐B1 was the most significant among all chromosomes. EMS mutants of TaGL1 possessed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…[ 77 ] As a member of FBN family, PAP6 is a homologue of FBN4 in Arabidopsis, [ 78 ] and was reported to regulate the expression of genes involved in cytokinins synthesis in Arabidopsis. [ 79 ] A recent study indicated that TaPAP6L modulated JA‐mediated grain size in wheat, [ 80 ] and may play an important role in wheat cold tolerance by VIGS. [ 17 ] In this study, we investigated a significant increase of JA content in TaSnRK1α−1A‐OE transgenic wheat lines and screened an interaction protein TaPAP6L‐2B that was possibly involved in JA synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 77 ] As a member of FBN family, PAP6 is a homologue of FBN4 in Arabidopsis, [ 78 ] and was reported to regulate the expression of genes involved in cytokinins synthesis in Arabidopsis. [ 79 ] A recent study indicated that TaPAP6L modulated JA‐mediated grain size in wheat, [ 80 ] and may play an important role in wheat cold tolerance by VIGS. [ 17 ] In this study, we investigated a significant increase of JA content in TaSnRK1α−1A‐OE transgenic wheat lines and screened an interaction protein TaPAP6L‐2B that was possibly involved in JA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Population Materials and Cold Tolerance Index: The wheat association panel, consisting of 243 wheat accessions, as we previously reported was planted at Yuanyang (35.04°N, 113.94°E) in 2017-2018 and 2019-2020 cropping seasons, and at Zhengzhou (34.87°N, 113.60°E) in 2017-2018 cropping season. [80,86] The F 10 RIL population (SC) containing 166 lines, developed from the cross of Shanghai3/Catbird×Naxos, was planted at Zhengzhou in 2015-2016 cropping season and at Yuanyang in 2017-2018 cropping season. No drought stresses occurred in field.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of 1BL.1RS translocation have been attributed to disease resistance genes such as Yr9, Pm8, Lr26, Sr31 and adaptation genes on the 1RS segment (Wieser et al, 2000). The genetic basis for the improvement of modern wheat cultivars includes the selection of major genes for vernalization response (Chen et al, 2013), photoperiod response (Würschum et al, 2018), kernel size (Cheng et al, 2020;Hanif et al, 2016;Ma et al, 2016;Niaz et al, 2023;Wang et al, 2015Wang et al, , 2016 and Fusarium head blight resistance (Wang et al, 2020). Therefore, uncovering the key genes related to yield, quality and disease resistance, and precisely pyramiding them will be the breakthrough in wheat improvement in the future.…”
Section: Breeding For Reduced Height Lodging and Disease Resistancementioning
confidence: 99%
“…Qgl1.hau.1B , a stable QTL for grain length with the PVE of 7.67%–14.45%, was fine mapped into a 0.98-Mb physical interval. The causal gene TaGL1-B1 encodes carotenoid isomerase and overexpression of which can enhance grain length through interaction with TaPAP6 ( Niaz et al, 2023 ). KL-PW is a major grain length gene at the P1 locus in Polish wheat, which encodes a MIKC-type MADS-box protein and significantly increased grain length of wheat ( Chai et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%